2019
DOI: 10.1111/and.13268
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long‐term paroxetine or bupropion treatment on puberty onset, reproductive and feeding parameters in adolescent male rats

Abstract: Antidepressant use in adolescents has become more common in recent years. We have found several studies stating that prenatal antidepressant exposure can lead to delayed or earlier puberty onset but there was no study on postnatal paroxetine or bupropion. The main aim of this study was to investigate the effect of postnatal exposure to bupropion or paroxetine on puberty onset, reproductive and feeding results. The male rats (n = 8/group) aged 21 days were exposed to paroxetine (3.6 mg/kg) or bupropion (17 mg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Unlike our study, Yardimci et al assessed the effects of long‐term paroxetine treatment on puberty onset in adolescent male rats. They reported that treatment with paroxetine did not result in any changes in the level of FSH, LH and leptin [ 46 ]. The reason for the difference between our results and others requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike our study, Yardimci et al assessed the effects of long‐term paroxetine treatment on puberty onset in adolescent male rats. They reported that treatment with paroxetine did not result in any changes in the level of FSH, LH and leptin [ 46 ]. The reason for the difference between our results and others requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Beeder et al also reported that selective serotonin reuptake inhibitors could negatively impact sperm quality in vitro , both in animal models and human studies (9). Other side effects of antidepressants could be associated to libido, delayed ejaculation or even impotence [ 9 , 12 , 13 ]. These off-target negative effects can lead to infertility, which in a vicious cycle is known to increase depressive and anxiety symptoms [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of common clinical drugs may lead to changes in the testicular microenvironment and thus affect spermatogenesis. In animal studies, it was found that bupropion ( Yardimci et al, 2019 ), paroxetine ( Erdemir et al, 2014 ; Yakubu and Atoyebi., 2018 ; Yardimci et al, 2019 ), benzodiazepines ( Chengelis et al, 1986 ; Means et al, 1982 ), nifedipine ( Iranloye et al, 2009 ; Lee et al, 2006 ), ethosuximide ( Lee et al, 2006 ), valproate ( Alsemeh et al, 2022 ; Nishimura et al, 2000 ; RØste et al, 2001 ; Sukhorum and Lamsaard., 2017 ), pregabalin ( Shokry et al, 2020 ; Taha et al, 2020 ), rosuvastatin ( Leite et al, 2017 ), etc., had negative effects on the testicular microenvironment. Antidepressant bupropion can cause testicular structural damage and interstitial edema ( Yardimci et al, 2019 ).…”
Section: Main Textmentioning
confidence: 99%
“…In animal studies, it was found that bupropion ( Yardimci et al, 2019 ), paroxetine ( Erdemir et al, 2014 ; Yakubu and Atoyebi., 2018 ; Yardimci et al, 2019 ), benzodiazepines ( Chengelis et al, 1986 ; Means et al, 1982 ), nifedipine ( Iranloye et al, 2009 ; Lee et al, 2006 ), ethosuximide ( Lee et al, 2006 ), valproate ( Alsemeh et al, 2022 ; Nishimura et al, 2000 ; RØste et al, 2001 ; Sukhorum and Lamsaard., 2017 ), pregabalin ( Shokry et al, 2020 ; Taha et al, 2020 ), rosuvastatin ( Leite et al, 2017 ), etc., had negative effects on the testicular microenvironment. Antidepressant bupropion can cause testicular structural damage and interstitial edema ( Yardimci et al, 2019 ). As a kind of selective serotonin reuptake inhibitors (SSRI), paroxetine can damage testicular structure, induce degeneration of seminiferous tubules, and cause vacuolization of germinal epithelium ( Erdemir et al, 2014 ; Yakubu and Atoyebi, 2018 ; Yardimci et al, 2019 ).…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation